UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QUR’AN HADIS MELALUI PEMBELAJARAN ACTIVE LEARNING TIPE INFORMATION SEARCH (PENELITIAN TINDAKAN KELAS)(Studi Lapangan di Mts Mazro’atul Ulum Citiis) - Wisnu Samsul Aripin; Mulyawan Safwandy Nugraha (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to improve student interest and learning outcomes in the subject of Al-Qur'an and Hadith through the implementation of Active Learning with the Information Search method. The research was motivated by low student interest, characterized by a lack of enthusiasm, activeness, and focus in learning, resulting in suboptimal learning outcomes. This study employed Classroom Action Research (CAR) with a qualitative approach at MTs Mazro'atul Ulum. The subjects were students in one of the MTs classes. The study was conducted through several cycles, including planning, implementation, observation, and reflection. Data collection techniques used observation and interviews, while data analysis was conducted using descriptive qualitative methods. The results showed that the implementation of Active Learning with the Information Search method increased student interest in learning, as evidenced by increased participation, attention, and active involvement in learning. This increased interest in learning positively impacted student learning outcomes, both in understanding the material and in relating the contents of the Quran and Hadith to everyday life. Thus, the Information Search type of Active Learning is effectively implemented to improve the quality of Al-Qur'an Hadith learning in Islamic Junior High Schools (Madrasah Tsanawiyah).